Pengaruh Political Visibility dan Environmental Performance terhadap Pengungkapan Informasi Lingkungan Hidup pada Perusahaan Publik di Indonesia - Ichsan Setiyo Budi (Jurnal Akuntansi dan Bisnis, 2009)
Companies are required to make disclosure environment because the company is seen by the public as major contributor to environmental problems that occur at this time. The purpose of this study was to provide empirical evidence of the influence of political visibility and environmental performance against the disclosure of environmental information on companies listed on the Stock Exchange in PROPER. The independent variables used in this research: environmental performance, and dependent variable: environment information disclosure. The results showed that the hypothesis in this study are supported by F test and only environment performance affects the disclosure of environmental information by t-test on companies listed on the Stock Exchange in PROPER